Odcienie i cienie wolontariatu - Włodarczyk, Ewa (My University, 2011)
Tekst poświęcony jest kwestii wolontariatu, szczególnie aktualnej w 2011 roku, który został ogłoszony Europejskim Rokiem Wolontariatu. Omówiono w nim prawne aspekty wolontariatu, statystyczne ilustracje praktyki wolontaryjnej oraz ich dynamikę i uwarunkowania na przestrzeni ostatniej dekady, a także próby ratowania idei wolontariatu we współczesnej Polsce. Ponadto tekst, oprócz wskazania pozytywnych aspektów wolontariatu, zachęca również do refleksji nad jego cieniami.

The article provides an analysis of voluntary service, which is particularly relevant in 2011, the European Year of Volunteering. The article discusses the main legal issues of volunteering, statistical data concerning voluntary service as well as their dynamics over the past decade. The article further documents attempts to promote the idea of voluntary services in contemporary Poland. Aside from showing the positive aspects of volunteering, the text also encourages reflection on its shadows.
Keywords: wolontariat; wolontariusz; volunteering; voluntary service; volunteer; voluntary activity; social forces; legal aspects of voluntary services in Poland